2023
DOI: 10.3390/foods12050948
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous Extraction of Bioactive Compounds from Olea europaea L. Leaves and Healthy Seed Oils Using Pressurized Propane

Abstract: Olive leaves (OL) are products of olive cultivation with a high commercial value because they contain valuable bioactive compounds. Chia and sesame seeds have a high functional value because of their attractive nutritional properties. When combined in the extraction process, the two products constitute a product of high quality. The use of pressurized propane in vegetable oil extraction is advantageous because it provides solvent-free oil. This study aimed to combine two high-quality products to obtain oils wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 56 publications
0
4
0
Order By: Relevance
“…These results are in agreement with the previously published data. It has been reported that simultaneous oil extraction from sunflower with olive leaves using solvents could increase the bioactive components of extracted oils (Jaski et al., 2022 , 2023 ). Also, oil extracted from pomegranate seeds with green tea leaves by cold press had higher total phenolic compounds (Dezashibi et al., 2022 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…These results are in agreement with the previously published data. It has been reported that simultaneous oil extraction from sunflower with olive leaves using solvents could increase the bioactive components of extracted oils (Jaski et al., 2022 , 2023 ). Also, oil extracted from pomegranate seeds with green tea leaves by cold press had higher total phenolic compounds (Dezashibi et al., 2022 ).…”
Section: Resultsmentioning
confidence: 99%
“…However, using olive leaves in the oil extraction could increase the induction period comparable with the rapeseed and soybean oils. There have been reports on the effect of olive leaves on the improvement of induction period of sunflower and sesame oils, which were extracted via simultaneous extraction by pressurized propane (Jaski et al, 2022(Jaski et al, , 2023. There are also reports that using rosemary and green tea incorporated with oilseeds while oil extraction by cold press could increase the oxidative stability of extracted oils (Ashrafi et al, 2023;Mikołajczak et al, 2021).…”
Section: F I G U R Ementioning
confidence: 99%
See 1 more Smart Citation
“…Currently, there is a concern about accomplishing greener procedures when extracting compounds of interest from agro-food matrices such as olives leaves, by employing greener extraction solvents such as water, 70:30 (v/v) water/ethanol solutions or deep eutectic solvents [37]. For olive leaves, in particular, recent works have proposed pressurized propane [38] or isopropanol water [39] for the extraction of bioactive compounds. The first approach is not adequate for polyphenols as they do not have a low boiling point.…”
Section: Introductionmentioning
confidence: 99%